Challenges with access to healthcare from the perspective of patients living with HIV: a scoping review & framework synthesis. Issue 8 (3rd August 2018) - Asghari, Shabnam; Hurd, Jillian; Marshall, Zack; Maybank, Allison; Hesselbarth, Lydia; Hurley, Oliver; Farrell, Alison; Kendall, Claire E.; Rourke, Sean B.; Becker, Marissa; Johnston, Sharon; Lundrigan, Phil; et al.
ABSTRACT: Accessing healthcare can be difficult but the barriers multiply for people living with HIV (PLHIV). To improve access and the health of PLHIV, we must consider their perspectives and use them to inform standard practice. A better understanding of the current literature related to healthcare access from the perspective of PLHIV, can help to identify evidence gaps and highlight research priorities and opportunities. To identify relevant peer-reviewed publications, search strategies were employed. Electronic and grey literature databases were explored. Articles were screened based on their title and abstract and those that met the screening criteria, were reviewed in full. Data analysis was conducted using a collaborative approach that included knowledge user consultation. Initial concepts were extracted, summarized and through framework synthesis, developed into emerging and final themes. From 20, 678 articles, 326 articles met the initial screening criteria and 64 were reviewed in full. The final themes identified, in order of most to least frequent were: Acceptability, Availability, Accessibility, Affordability, Other Barriers, Communication, Satisfaction, Accommodation, Preferences and Equity in Access. The most frequently discussed concepts related to negative interactions with staff, followed by long wait times, limited household resources or inability to pay fees, and fear of one's serostatus being disclosed. Knowledge users were in agreement with the categorization of initial concepts and final themes; however, some gaps in the literature were identified. Specific changes are critical to improving access to healthcare for PLHIV. These include improving availability by ensuring staff and healthcare professionals have proper training, cultivating acceptability and reducing stigma through improving HIV awareness, increasing accessibility through increased HIV information for PLHIV and improved dissemination of this information to increase patient knowledge and health awareness. Finally, ensuring proper protocols are implemented and followed to guarantee patient confidentiality and overall satisfaction with healthcare services are recommended.